Faktor-faktor Pemerolehan Bahasa Anak Pada Umur 2-4 Tahun - Azhari, M. Nazar Al; Nadina, Diya Amalia; Indriani, Windy (UPA Bahasa Universitas Tidar And HISKI Kedu, 2025)
This study focuses on the factors of language acquisition in children aged 2-4 years. This age was chosen because it is a critical period where children actively absorb language and often make mistakes in its use. This study uses a descriptive approach by collecting data through direct interviews with the child's parents. The data obtained were then transcribed, analyzed, and presented in the form of a written report. The factors that influence children's ability to learn a language are very diverse. Early age is the golden period for learning a language, where the child's brain is very responsive to language input. The surrounding environment, especially family and peers, has a big influence because children tend to imitate the language they hear every day. In addition, the first language mastered by the child also plays an important role in the subsequent language learning process. Strong motivation is also the key to success in learning a new language. All of these factors are interrelated and work together to shape children's language skills. The process of learning a language is natural and normal, and children's language skills will continue to develop with age and experience.